2007
DOI: 10.1177/039139880703001009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Direct Hemoperfusion Using a Polymyxin-B Immobilized Column in Solid Organ Transplanted Patients with Signs of Severe Sepsis and Septic Shock. a Pilot Study

Abstract: Background Polymyxin B (PMX-B) is a polycationic antibiotic, known to bind the lipid A portion of endotoxin, a cell wall component found exclusively in gram negative bacteria (GNB). An extracorporeal hemoperfusion device (TORAYMYXIN) has been developed: PMX is covalently bound on the surface of an insoluble carrier material so that the endotoxin can be inactivated in the blood without exerting its toxicity on the brain and kidney The aim of this study was to clarify the efficacy, safety and clinical effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Improvement in blood pressure and reduction in vasopressor doses have also been demonstrated in other studies. 29,30 In our study, even as the dose of vasoactive agents (indicated by the inotropic score) was reduced, there was a significant increase in MAP in the polymyxin B hemoperfusion group at 72 hours (Table 3). Accordingly, the vasopressor dependency index decreased significantly in the polymyxin B hemoperfusion group but not in the conventional therapy group.…”
Section: Polymyxin B-immobilized Fiber Column In Abdominal Sepsismentioning
confidence: 52%
See 1 more Smart Citation
“…Improvement in blood pressure and reduction in vasopressor doses have also been demonstrated in other studies. 29,30 In our study, even as the dose of vasoactive agents (indicated by the inotropic score) was reduced, there was a significant increase in MAP in the polymyxin B hemoperfusion group at 72 hours (Table 3). Accordingly, the vasopressor dependency index decreased significantly in the polymyxin B hemoperfusion group but not in the conventional therapy group.…”
Section: Polymyxin B-immobilized Fiber Column In Abdominal Sepsismentioning
confidence: 52%
“…The results of our study shed light on this controversial matter. In this RCT of surgical patients with septic shock and severe sepsis induced by abdominal sepsis, polymyxin B hemoperfu- .50 6 (20) 8 (30) .50…”
Section: Commentmentioning
confidence: 99%
“…Sepsis can directly induce AKI without the need of hemodynamic instability. 36 Mortality was not assessed. 34 The Early Use of Polymyxin B Hemoperfusion in Abdominal Sepsis (EUPHAS) study was recently published and was relatively unique as it was targeting a population that was likely to exhibit high circulating levels of endotoxin and in whom the source of sepsis was definitely cured by initial surgery.…”
Section: New Membranes Dedicated For Sepsis and Sirs: High Selective mentioning
confidence: 99%
“…PMX B treatment was also studied in solid organ transplant patients with severe sepsis and septic shock. Despite three PMX sessions, no hemodynamic improvement was noticed [ 74 ]. Mortality was not assessed in this population.…”
Section: Polymyxin-coated Membranementioning
confidence: 83%